Private cloud storage implementation using OpenStack Swift - Agustinus Noertjahyana; Juan Reno; Henry Novianus Palit; Justinus Andjarwirawan (Universitas Ahmad Dahlan, 2019)
The use of distributed and parallel computer systems is growing rapidly, requiring an appropriate system to support its work processes. One technology that supports distributed computer systems is cloud computing. This system can generate the need to maximize the use of existing computing resources, one of which is in the form of cloud-based storage. The computer laboratory of Informatics Department of Petra Christian University has very large resources, but they have not been optimized in the utilization of existing storage devices. This condition gives the idea to utilize computers in the laboratory with cloud, so the storage can be used well. This implementation used the OpenStack cloud framework, which could provide IaaS service. From some existing OpenStack services, storage management used OpenStack Swift on its processing. OpenStack Swift is a cloud-based storage service that leverages various computing resources. After the implementation process, testing was done by way of data management, so storage could store, retrieve, and delete data. In addition, testing was also done by turning off some physical machines to ensure cloud services could remain well accessible, and measure the speed of data transfer in cloud storage. The resulting data was used to evaluate the cloud storage systems that had been created.